Factors affecting employee engagement : case study at SIRIM Berhad and Telekom Malaysia Berhad - Othman, Siti Nor Haizum (2010)
This paper presents a case study in Sirim Berhad and Telekom Malaysia Berhad, which emphasize the factors affecting employee engagement in the organisations. In line with the current world business development nowadays, the good and successful management of job engagement within any organization are considered to be critical in order to increase the productivity of employee. The increasing of disengaged workers also in part contributes to the highly turnover and thus became one of the main reasons underlying the issue of retention these days. Unfortunately, there are limited researches on employee engagement in the management literature. The concept of employee engagement and its drivers were conducted primarily within western countries. Simply put, this research was done based on certain problems identified which can boost engagement level among workers in Malaysia to enhance their work performance. This study provides several factors that explain the variation in employee engagement within two organisations. Questionnaire was used as an instrument to collect data. The particular software applied was SPSS in Windows environment